Libido–sexual disorders and abandonment of injectable contraceptives among users of the Ivorian Association for Family Well-Being in Korhogo, Côte d’Ivoire - Essis, Esme Marie-Laure; Yeo, Katienin Jeanne; Amalaman, Djedou Martin; Konan, Loukou Leandres; Bamba, Iba; Coulibaly, Koné S. Aminata; Kpebo, D. Olga Denise; Orsot, Tetchi; Delafosse, Joseph; Aka, Joseph (Frontiers in Global Women's Health, 2023)
Introduction The recent introduction of modern contraceptive methods in resource-limited countries is confronted with the occurrence of undesirable effects that hinder their use in the long term. This study conducted among the users of the Ivorian Association for Family Well-Being in Korhogo describes the libido–sexual problems associated with the discontinuation of injectable contraceptives in former users. The objective of the study was to identify the factors that led to the abandonment of injectable contraceptives among female users of the Ivorian Association for Family Well-Being in Korhogo between 2018 and 2019. Materials and methods Qualitative data were collected from 15 former users (24–38 years old) of injectable contraceptives duration of 2–3 months. Additional data were collected from five health workers aged 35–60 years. In-depth interviews were conducted to explore the experience with injectable contraceptives and reasons for discontinuation. Following data collection, audio-recorded data were transcribed, translated, and coded using thematic analysis through an inductive approach. Results Side effects identified as associated with injectable contraceptives include libido–sexual disorders, unusual bleeding, and weight gain. The most common reason for discontinuation were libido–sexual disorders, which impacted the households’ intimacy and provoked their abandonment or the change of contraceptive methods among injectable contraceptive users. Conclusion Adverse events were dominated by libido–sexual disorders, unusual bleeding, and weight gain leading to the abandonment or change of the contraceptive. These results suggest points of intervention for increasing continuation among users. This intervention should include training of health workers to investigate and manage adverse events related to the use of injectable contraceptives and the improvement of communication between health workers and users on adverse events of injectable contraceptive use.